Lixiviación de minerales carbonaceos con tiosulfato de amonio para la recuperación de metales preciosos de oro y plata. - Custodio Avalos, David Angel (2014)
In Peru there are multiple mining gold deposits contaminated with carbonaceous ore, this contaminated mineral does not allow leaching with sodium cyanide, because the gold-cyanide complex formed is adsorbed by the organic carbon found in the ore, producing a pregrobbing effect; therefore achieved searches other treatment methods, one of which leaching with ammonium thiosulfate. This research project's main objective is to investigate possible solutions to the problem presented in these carbonaceous minerals found in various mining sites in the country. B experimental level by leaching tests, both laboratory scale and pilot scale seek to find a suitable process that goes hand in hand with a very high technical and economic profitability. In this research project in which we intend to design a process for recovery of precious metals from carbonaceous minerals which find the optimal conditions of the leaching process, then undertake the design and sizing of equipment required, taking into account the reagents ( thiosulfate and copper), and the parameters and process variables chosen.